MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION DAN ING NGARSA SUNG TULADHA - Siburian, Lilis Apriliani; Saija, Louise (LPPM Universitas Advent Indonesia, 2019)
Mathematical communication ability is one of the mathematical ability in learning mathematics. This comparative design research aimed to see whether the mathematical communication enhancement of students who acquire Ing Ngarsa Sung Tuladha learning model is significantly better than students who acquire Cooperative Integrated Reading and Composition learning model. The sample in this research are students of two grade 7th classes in SMP Negeri 5 Lembang, Bandung Barat. Students in class VII-D acquire Cooperative Integrated Reading and Composition learning model, and students in class VII-B acquire Ing Ngarsa Sung Tuladha learning model. Results of this study showed that the students’ mathematical communication enhancement, both who acquire Cooperative Integrated Reading and Composition or Ing Ngarsa Sung Tuladha learning model categorized as “moderate”. More further, the mathematical communication enhancement of students who acquire Ing Ngarsa Sung Tuladha learning model is significantly better than students who acquire acquire Cooperative Integrated Reading and Composition learning model. Another result is that students like the learning model, either Cooperative Integrated Reading and Composition or Ing Ngarsa Sung Tuladha. Key Words: Mathematical Communication, Cooperative Integrated Reading and Composition, Ing Ngarsa Sung Tuladha.